Comportamento da areia de britagem de rocha calcária na argamassa de revestimento - Tokarski, Rosângela Basso (2017)
The goal of this resarch is to identify the behavior of limestone crushed sand in coating mortar. Five trace compositions were proposed and tested: the first one made up of 100% natural sand, which will be used as reference trace, the second composition presented 80% natural sand and 20% limestone rock crushed sand, the third one 60% natural sand and 40% limestone rock crushed sand, the fourth one with 40% natural sand and 60% limestone rock crushed sand, and the fifth trace 20 % natural sand and 80% limestone rock crushed sand. The mortar traces were composed of cement, sand, water and additive, without the presence of lime, and these were tested in the wet and hardened state and presented the following results: Composite traces with limestone rock crushed sand presented better performance than the reference trace, which had only natural sand. The traces with 60% natural sand and 40% limestone crushed sand showed better performance in 70% of the tests performed, and presented a grain size curve within the optimal upper and lower zone, as required by the standard rules. The relevance of this study is due to the fact that crushed sand is a waste that generates important environmental liability, and natural sand extraction leads to the environmental degradation. Using crushed sand to replace natural sand is one way to contribute to environmental preservation.